ANALISIS PREFERENSI SISWA MELANJUTKAN KE SMAN 3 KECAMATAN TUALANG KABUPATEN SIAK TAHUN AJARAN 2014/2015 - Yusuf, Sardi Yusuf Sardi; Arlizon, Raja arlizon Raja; ', Nurasmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT This research aim to to know internal factor and student eksternal in chosening SMA. As for Internal factor of him is 1. Wishing to continue to high Teacher 2. Wish to obtain;get competent work 3. Aspiration 4. Value report which enough support 5. Want to be man of science 6. Desire alone. As for base consideration of election a factor school of Ekternal is 1. Ability of economics 2.Family motivation 3. Follow friend 4. easy School location [in] accessing 5. Get more public science. Method weared in this research is Rendom sampling that is where its election [pass/through] toss thrown paper. its Data Tekni with enquette with student sampling of SMAN 3 Tualang amounting to 112 student people. Keyboard : Preferensi, Minat